Experimental and numerical study on the cracking behavior and flexural strength of RC shallow beams with rectangular opening and varying length. (June 2022) - Jebasingh Daniel, J.
Abstract: In Ethiopia, the two way beam floor system gains popularity in building construction patterns where large column free space is mandatory, whose beam slenderness ratio is less than 15. The provision of mechanical and electrical line services in these beams is handled by a non-engineered manner of organizing elongated openings to enhance the regimented compact service network, due to the shortcoming of code. Hence, this paper deals with an experimental investigation on the cracking behavior, load–deflection behavior, and failure mode of beams with elongated openings whose slenderness ratio is less than 15 to formulate an engineered pattern. The experimental results are validated by performing numerical computations using finite element software. The specimens are tested under two point loading and the effect of opening under the varying length is studied in terms of first crack load, ultimate load, flexural strength, deflections, and failure load.